2001
DOI: 10.1038/sj.ejcn.1601198
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in fat-free mass, skeletal muscle, body cell mass and fat mass between 18 and 94 years

Abstract: Objective: To determine (1) lean and fat body compartments, re¯ected by fat-free mass (FFM), appendicular skeletal muscle mass (ASMM), body cell mass (BCM), total body potassium (TBK), fat mass and percentage fat mass, and their differences between age groups in healthy, physically active subjects from 18 to 94 y of age; and (2) if the rate of decrease in any one of the parameters by age might be accelerated compared to others. Methods: A total of 433 healthy ambulatory Caucasians (253 men and 180 women) aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
235
4
15

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(271 citation statements)
references
References 35 publications
17
235
4
15
Order By: Relevance
“…21,22,26 This was confirmed in our analysis showing an increase of the FMI with age group in the lowest quartiles of the FMI (Figures 1a and b). Longitudinal observations in an elderly population have shown that total body weight remains stable, but masks an increase in FM and a decrease in FFM.…”
Section: Discussionsupporting
confidence: 74%
“…21,22,26 This was confirmed in our analysis showing an increase of the FMI with age group in the lowest quartiles of the FMI (Figures 1a and b). Longitudinal observations in an elderly population have shown that total body weight remains stable, but masks an increase in FM and a decrease in FFM.…”
Section: Discussionsupporting
confidence: 74%
“…Aging is associated with an increase in fat mass (FM) and a decrease in fat-free mass (FFM) (Roubenoff, 2000;Kyle et al, 2001). While the health implications of FM expansion are known from many years, those of FFM depletion have started to be investigated only recently (Kennedy et al, 2004;Jensen, 2005;Kyle et al, 2005;Villareal et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Data are taken in men from studies performed on subjects with varying age and classified as <60, 60-75, >75 years (3,14,15,16) Obesity should be defined as the amount of excess fat storage associated with elevated health risk. Since many health risks, including osteo-arthritis (4), loss of autonomy (13), and decreased quality of life are associated with increased fatness in the elderly, it may be more appropriate to define obesity on fatness than on BMI.…”
Section: Figurementioning
confidence: 99%